1984
DOI: 10.1063/1.333851
|View full text |Cite
|
Sign up to set email alerts
|

Pressure and temperature dependence of the electromechanical properties of polarized polyvinylidene fluoride films

Abstract: The piezoelectric resonance method was adopted in order to measure piezoelectric and elastic constants of polyvinylidene fluoride films over the temperature range from −40 to 60 °C and at pressure up to 3 kbar. We have shown that the glass transition temperature increases with pressure, dTg/dP being approximately equal to 17 °C/kbar at atmospheric pressure. We have demonstrated that the electromechanical coupling factor K32 is not independent of temperature. Previous measurements, carried out at atmospheric pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Finally, the piezoelectric response of the multiferroic composites increases with temperature due to the increased mobility of the molecular dipoles in the polymer [29,30]. It is worth noting that the piezoelectric behaviour is similar in all the composites.…”
Section: Resultsmentioning
confidence: 90%
“…Finally, the piezoelectric response of the multiferroic composites increases with temperature due to the increased mobility of the molecular dipoles in the polymer [29,30]. It is worth noting that the piezoelectric behaviour is similar in all the composites.…”
Section: Resultsmentioning
confidence: 90%
“…2a shows that the piezoelectric voltage under the same mechanical loading changes linearly with temperature. The increase of piezoelectric coefficient d 33 of PVDF with temperature (between the glass transition temperature (−40 °C) and the breakdown of the piezoelectric film (80 °C)) is a well-known phenomenon (Destruel et al, 1984;Guthner et al, 1992;Faust and Lakes, 2015). Note that this is independent of the pyroelectric effect.…”
Section: Piezoelectric and Pyroelectric Effect Of Pvdfmentioning
confidence: 92%
“…Several different mechanisms may contribute to this phenomenon. First, the higher temperature will cause a decrease of the stiffness of the polymer and therefore larger deformation will result from a same loading (Destruel et al, 1984;Guthner et al, 1992); a recent study indicated that the change of stiffness is not the only reason and their analysis indicates that flexoelectric effect may also play a role, especially when the PVDF is mounted on a non-polymer material such as aluminum used in this study (Faust and Lakes, 2015). The thermal stress on the voltage was included in the entire voltage.…”
Section: Piezoelectric and Pyroelectric Effect Of Pvdfmentioning
confidence: 99%
“…11 This coefficient is also associated with other names such as piezoelectric d 33 coefficient [12][13][14][15][16] or electromechanical d 33 coefficient. [20][21][22] This group of polar polymers is also categorized as piezoelectric materials and their behavior is named "ferroelectric. Classical piezoelectric systems include crystals such as quartz, topaz, and special ceramics, as well as natural materials such as silk, bone, collagen, and DNA (a nucleic acid carrying the genetic information in cells).…”
Section: Piezoelectric Propertiesmentioning
confidence: 99%
“…20 Poly(vinylidene fluoride) (PVDF), as a polar polymer, showed strong piezoelectric properties and was widely used. [20][21][22] This group of polar polymers is also categorized as piezoelectric materials and their behavior is named "ferroelectric. "…”
Section: Piezoelectric Propertiesmentioning
confidence: 99%